Strategi Pengembangan Jaringan Bisnis Say Risolle Melalui Platform E-Commerce - Resya Dwi Marselina; Taufik Purnama Hidayat; Anisa Rahman; Rama Anugrah; Tisa Yulisti Suherliatisyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is driven by business networks that are developing in the business world and giving rise to intense commercial competition. To answer this, the author conducted research on the business network carried out by Say Risolle MSMEs involving distributors, e-commerce and consumers. The aim of this research is to find out what the founders of Say Risolle did in building their business network and to study how Say Risolle was marketed. This research was conducted directly with the founder of Say Risolle who is also the author of this research. This research examines how the business network implemented by pioneer Say Risolle for product development starts from marketing until the product is marketed to consumers. This research uses qualitative methods, specifically observing Say Risolle's operational areas at the location level, actors, commercial activities and marketing strategies that will be carried out by Say Risolle through the e-commerce platform.